Alpine ice-core evidence for the transformation of the European monetary system, AD 640–670. (14th December 2018) - Loveluck, Christopher P.; McCormick, Michael; Spaulding, Nicole E.; Clifford, Heather; Handley, Michael J.; Hartman, Laura; Hoffmann, Helene; Korotkikh, Elena V.; Kurbatov, Andrei V.; More, Alexander F.; Sneed, Sharon B.; Mayewski, Paul A.
Abstract: Abstract : The seventh-century AD switch from gold to silver currencies transformed the socio-economic landscape of North-west Europe. The source of silver, however, has proven elusive. Recent research, integrating ice-core data from the Colle Gnifetti drill site in the Swiss Alps, geoarchaeological records and numismatic and historical data, has provided new evidence for this transformation. Annual ice-core resolution data are combined with lead pollution analysis to demonstrate that significant new silver mining facilitated the change to silver coinage, and dates the introduction of such coinage to c . AD 660. Archaeological evidence and atmospheric modelling of lead pollution locates the probable source of the silver to mines at Melle, in France.